Education on The Environmentally Friendly Utilization of Household Waste Use - Junainah Junainah; Oktaviani Oktaviani; Bunga Permata Mentari; Retno Meitasari; Afriyani Afriyani (Altifani Journal: International Journal of Community Engagement, 2025)
ABSTRACT. This Community Service (PKM) activity was carried out at Nurul Ilmi Junior High School, Banyuasin Regency, with the aim of enhancing students’ knowledge and skills in utilizing household waste to support environmentally friendly agricultural practices. The program emphasized the use of coconut fiber as a natural growing medium and used plastic cups as low-cost alternative planting containers. The implementation included educational sessions on types of household waste that can be repurposed, demonstrations of producing planting pots from used plastic cups, and hands-on practice in preparing planting media using coconut fiber. Fifty students are actively involved in the process of shredding coconut fiber, preparing the growing medium, and planting seedlings, allowing them to understand each stage of practical waste-utilization techniques. The results indicated an improvement in students’ understanding of organic and inorganic waste recycling, as well as their ability to create simple and functional planting pots. In addition, the program successfully increased students’ motivation to develop planting activities within the school environment. Overall, this PKM activity fostered environmental awareness through the application of the principles of reduce, reuse, and recycle (3R), while demonstrating that coconut fiber and used plastic cups are effective, accessible, and environmentally friendly planting media.